Peningkatan Keterampilan Menulis Teks Tanggapan Deskriptif Melalui Teknik Kalimat Mengalir Dengan Menggunakan Media Gambar - Destysia Ayu Ardira; Rosita Ambarwati; Herman Trisna (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Writing is communication that is used to express ideas or concepts in written form. When writing, you need the ability to express thoughts, concepts and experiences to make writing easier. However, after observations were made in class VII C regarding writing, namely writing response texts, it turned out that there were still many students who were lazy, lacked enthusiasm, had difficulty expressing ideas, liked playing games, and were less interested in writing response texts. Therefore, action is needed to improve students' writing skills. The aim of this research is to describe the improvement in skills in writing descriptive response texts through flowing sentence techniques with image media in class VII C students at SMP Negeri 3 Madiun. The learning process is carried out through two cycles, namely cycle I and cycle II. The results of this study showed that the class average score on the pre-cycle knowledge test was 63.47. In cycle I there was an increase of 78 or in the quite good category and in cycle II there was another increase of 84 or in the good category. The increase in writing descriptive response texts was also followed by changes in students' learning attitudes towards a better direction during the learning process of writing descriptive response texts using flowing sentence techniques using image media.